Treatment with intravenous melphalan and dexamethasone is not able to overcome the poor prognosis of patients with newly diagnosed systemic light chain amyloidosis and severe cardiac involvement - Dietrich, Sascha; Schönland, Stefan; Benner, Axel; Bochtler, Tilmann; Kristen, Arnt; Beimler, Jörg; Hund, Ernst; Zorn, Markus; Goldschmidt, Hartmut; Ho, Anthony Dick; Hegenbart, Ute (Blood, 2010)
Treatment with oral melphalan and dexamethasone (M-Dex) was reported to be effective and feasible in patients with systemic light chain amyloidosis (AL) not eligible for high-dose melphalan. We report on 61 patients with advanced AL who were treated with intravenous M-Dex as first-line therapy. Estimated median overall survival (OS) was 17.5 months. Seventeen patients (28%) died within 3 months, mostly of disease-related complications. In addition, nonhematologic toxicity of Common Terminology Criteria grade 3 or 4 was observed in 20 patients, whereas hematologic toxicity was low. Twenty-seven patients (44%) had hematologic response, including complete in 7 patients (11%) and partial remission in 20 patients (33%). Organ response was observed in 15 patients (25%). The amount of the involved free light chains in serum and Karnofsky Index at diagnosis significantly influenced OS. Plasma levels of the cardiac biomarkers before start of treatment and their increase after the third M-Dex cycle also were strong negative predictors of OS. These parameters might help to identify patients who will not benefit from M-Dex chemotherapy.